Organophosphate esters (OPEs) in a coral reef food web of the Xisha Islands, South China Sea: Occurrence, trophodynamic, and exposure risk. (February 2023) - Kang, Yaru; Zhang, Ruijie; Yu, Kefu; Han, Minwei; Li, Haolan; Yan, Annan; Liu, Fang; Shi, Jingwen; Wang, Yinghui
Abstract: Despite organophosphate esters (OPEs) are widely prevalent in the environment, however, limited information is available regarding their occurrence, trophodynamics, and exposure risks in coral reef ecosystems. In this study, 11 OPEs were investigated in a tropical marine food web (7 fish species and 9 benthos species) from the Xisha (XS) Islands, South China Sea (SCS). The ∑11 OPEs were 1.52 ± 0.33 ng/L, 2227 ± 2062 ng/g lipid weight (lw), 1024 ± 606 ng/g lw, and 1800 ± 1344 ng/g lw in seawater, fish, molluscs, and corals, respectively. Tris (2-chloroisopropyl) phosphate (TCIPPs) were the dominant OPEs in seawater, fish, and molluscs, while tris (2-butoxyethyl) phosphate (TBOEP) predominated in coral tissues. Abiotic and biotic factors jointly affect the OPEs enrichment in marine organisms. Trophic magnification factors (TMFs) (range: 1.31–39.2) indicated the biomagnification potency of OPEs. A dietary exposure risk assessment indicated that OPEs at current levels in coral reef fish posed a low risk to human health but were not negligible. Overall, this study contributes to a further understanding of the environmental behaviors of OPEs in coral reef ecosystems. Graphical abstract: Image 1 Highlights: OPEs profiles in seawater and marine organisms are different. Fish tend to enrich Cl-alkyl OPEs and benthos prefer to accumulate aryl OPEs. Abiotic and biotic factors jointly affect the OPEs enrichment in marine organisms. OPEs pose a low risk to human health by coral reef fish ingestion. Emerging pollutants are dominating the pollution status in the Xisha Islands.